European Code against Cancer 4th Edition: Alcohol drinking and cancer. (December 2016) - Scoccianti, Chiara; Cecchini, Michele; Anderson, Annie S.; Berrino, Franco; Boutron-Ruault, Marie-Christine; Espina, Carolina; Key, Timothy J.; Leitzmann, Michael; Norat, Teresa; Powers, Hilary; Wiseman, Martin; Romieu, Isabelle
Abstract: Alcohol consumption is the third leading risk factor for disease and mortality in Europe. As evaluated by the International Agency for Research on Cancer (IARC) Monographs, a causal relationship is established for consumption of alcoholic beverages and cancers of the oral cavity, pharynx, larynx, oesophagus, liver, colorectum and female breast, even at low and moderate alcohol intakes. The higher the amount of alcohol consumed, the higher the risk of developing cancer. In Europe, an estimated 10% (95% CI: 7%–13%) of all cancer cases in men and 3% (95% CI: 1%–5%) of all cancer cases in women are attributable to alcohol consumption. Several biological mechanisms explain the carcinogenicity of alcohol; among them, ethanol and its genotoxic metabolite, acetaldehyde, play a major role. Taking all this evidence into account, a recommendation of the 4th edition of European Code against Cancer is: "If you drink alcohol of any type, limit your intake. Not drinking alcohol is better for cancer prevention."